The Guillotine as an Aesthetic Idol and Kant's Loathing - Vinogradovs, Valerijs (Sophia, 2016)
Kants doctrine of aesthetic ideas, along with his brief treatment of ugliness, has been the focus of some recent literature. In this paper, I employ an original approach, which nonetheless draws from Kants oeuvre, to pin down the phenomenological complexity of a spectacular event that took place at the inception of the French Terrorthe decapitation of Louis the XVI. To this end, the first section of the essay fleshes out an interpretative framework explicating how seeing the guillotine as an aesthetic idea could serve as a means to actualise the revolutionary ideal. The second section introduces a reading of Schwärmerei and argues that this unruly genius is accountable for the creation of aesthetic idols, rendering a spurious aesthetic experience. Finally, in the last section, I argue that there is a significant distinction between Kants account of ugliness and loathing, and that the latter stands for neither a moral nor an aesthetic response to a morally repellent object, but rather is an extraordinary sensible response.